Noise stability of diversity system for signals PSK and DPSK in multipath channels - G. M. Sidelnikov; D. V. Ognev (Омский научный вестник, 2018)
We consider noise stability of diversity system for signals PSK and DPSK in multipath channels with additive Gaussian noise. The analysis of noise stability is based in fluctuation of signal distance through multipath. Detailed analysis compares algorithms of diversity system of diversity. There are calculated curves of finite noise stability from PSK and DPSK for channels with different of diversity system. The obtained characteristics of signal distance determine the effectiveness of signals in different channels, as well as the analysis of noise immunity at various levels of additive noise determine the possibility of applying such channels as diversity reception, and the transmission.